The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/978-1-4939-8697-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Platforms and Techniques to Study Stem Cell Metabolism

Abstract: Over the past decade, advances in systems biology or 'omics techniques have enabled unprecedented insights into the biological processes that occur in cells, tissues, and on the organism level. One of these technologies is the metabolomics, which examines the whole content of the metabolites in a given sample. In a biological system, a stem cell for instance, there are thousands of single components, such as genes, RNA, proteins, and metabolites. These multiple molecular species interact with each other and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Proton NMR ( 1 H-NMR), gas chromatography–mass spectrometry, and imaging mass spectrometry were done according to established protocols ( 53 , 54 ). We used BLI, an optical label-free technology, to examine interactions between the TLX LBD and different fatty acids.…”
Section: Methodsmentioning
confidence: 99%
“…Proton NMR ( 1 H-NMR), gas chromatography–mass spectrometry, and imaging mass spectrometry were done according to established protocols ( 53 , 54 ). We used BLI, an optical label-free technology, to examine interactions between the TLX LBD and different fatty acids.…”
Section: Methodsmentioning
confidence: 99%
“…One of the major issues is the choice of fixatives, because different fixatives such as glutaraldehyde, paraformaldehyde, and cryopreservant materials such as sucrose should be avoided as they frequently affect lipids and other metabolites in the tissue. The optimal fixation method for metabolic imaging is flesh freezing in liquid nitrogen, but care needs to be taken to ensure complete freezing while avoiding tissue cracking (Tang et al, 2018). In case of brain organoids that are very small (~1-2 mm in diameter), submerging them in liquid nitrogen disintegrates them.…”
Section: Msi Protocol Suitable For Human Brain Organoidsmentioning
confidence: 99%
“…One of the new technologies not yet utilized for brain organoid studies is mass spectrometry imaging (MSI)-or imaging mass spectrometry-that uses mass spectrometry to directly resolve information on the molecular composition of complex biological samples in a single experiment (Watrous et al, 2011;Seeley et al, 2011;Caprioli RM, 2016;Tang et al, 2018;Chen et al, 2019;Spruill et al, 2022). MSI has emerged as a powerful molecular imaging technology, bringing unparalleled molecular specificity and sensitivity to map the distribution of small molecules in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Each organoid is grown at atmospheric O 2 conditions and physiologic pH of 7.25 and can last up to 18 months in culture. A detailed analysis is underway to examine molecular, metabolic, cellular, and physiological properties of the different cell types that are part of the neurogenic niche (56,57). The 3D human brain organoid model can be used in a high-9 throughput manner for assessing novel small molecules that promote neural stem cell selfrenewal and neurogenesis or decreased microglial inflammation, thus targeting multiple elements of the neurogenic niche.…”
Section: Nervous Systemmentioning
confidence: 99%
“…By using this mouse model, they demonstrated that exposure to Mars mission-relevant doses of SPE protons or GCR ions profoundly affects human hematopoiesis and introduces mutations in genes associated with hematopoiesis distinct from those induced by gamma radiation. Perhaps most concerning is that exposure to some of the higher energy HZE ions, e.g., 56 Fe ions, resulted in the generation of human T-cell acute lymphoblastic leukemia in vivo (82). This ability to reconstitute human hematopoiesis and perform in vivo exposures to Mars mission equivalent doses and ion species of radiation provides a powerful experimental model system that can be used to explore possible LET effects.…”
Section: Hematopoietic Systemmentioning
confidence: 99%